Hydroxyapatite/F-75 functionally graded biomaterials fabricated by powder metallurgy - Noorazimah Mohd Ab Llah (School of Materials Engineering, 2012)
This study has focused on a research of functionally graded materials (FGMs) HAP/F-75 fabricated by powder metallurgy technique. Powder metallurgy is an attractive and versatile route for fabrication of FGM because of its large opportunity for compositional and microstructural control. In this research, HAP/F-75 functionally graded materials with three layers were fabricated. The effect of different composition in the intermediate layer of FGM on physical and mechanical properties and also biocompatibility has been studied.